Pengetahuan, Sikap, dan Dukungan Keluarga dengan Minat Imunisasi Measles Rubella di Kelurahan Bukit Wolio Indah Kota Baubau - taswin, Taswin; Azis, Waode Azfari; Wahyuddin, Wahyuddin; Erni, Erni; ,; Meilani, Ni'ma (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2020)
Measles, or known in Indonesian as measles, and Rubella, are two infectious diseases that are contagious. Data for 2018 MR immunization coverage until the end of november only reaches (73.7%) and Measles Immunization trends tend to fluctuate in Bukit Wolio Indah Kelurahan. This happens because of various factors namely mother's knowledge, attitudes, and family support which have been formulated as the reason of the many factors. This study aims to determine how the relationship of knowledge, attitudes, and family support to the interest of MR immunization in the Bukit Wolio Indah Village, Baubau City. This type of research is analytical survey with cross sectional approach, and uses simple random sampling technique. The number of samples in the study were 70 respondents. The analysis used was univariate and bivariate analysis at 95% confidence level (α = 0.05). Chi square test results obtained from the study that knowledge of MR immunization interests (ρ = 0.005), attitudes with MR immunization interests (ρ = 0.004), and family support with MR immunization interests (ρ = 0.273). The conclusion from this study there is no relationship on the family support variable, and there is a relationship on the attitude and knowledge variables with the interest of MR immunization in Bukit Wolio Indah Village, Baubau City. Suggestions that health practitioners can better socialize to the public about the benefits of MR immunization.